Anomalous I-V curve for mono-atomic carbon chains - SANVITO, STEFANO (My University, 2010)
The electronic transport properties of mono-atomic carbon chains were studied theoretically using a combination of density functional theory and the non-equilibrium Green's functions method. The I?V curves for the chains composed of an even number of atoms and attached to gold electrodes through sulfur exhibit two plateaus where the current becomes bias independent. In contrast, when the number of carbon atoms in the chain is odd, the electric current simply increases monotonically with bias. This peculiar behavior is attributed to dimerization of the chains, directly resulting from their one-dimensional nature. The finding is expected to be helpful in designing molecular devices, such as carbon-chain-based transistors and sensors, for nanoscale and biological applications.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; mono-atomic carbon chains; Nanoscience & Materials